NETWORK GOVERNANCE DALAM PENINGKATAN IPM PEREMPUAN DI KABUPATEN WONOGIRI - Rossilawati, Risky Shinta; Hanani, Retna; -, Kismartini (Journal of Public Policy and Management Review, 2024)
One of the benchmarks for human development can be seen from the HDI. In the last 5 years, the HDI for Wonogiri regency shows that the HDI for women has lagged behind the HDI for men. Starting from these problems, the Government of Wonogiri Regency is trying to increase the HDI for women by involving multi-sectoral actors. The involvement of multi-sectoral actors raises complex relationships between actors which are then theoretically referred to as network governance. This study aims to analyze the process of network governance whether it has been implemented optimally or not by actors, as well as to analyze the driving factors for the formation of network governance. This study uses network governance theory from Klijn & Koppenjan with 4 indicators of analysis, namely Actor, Interdependency and Frames, network management, institutional features and Interaction & Complexcity: output. The research method used is descriptive qualitative method with data collection through interviews and literature study. The results of the study show that the network governance process in an effort to increase the HDI of women in Wonogiri Regency has not been implemented optimally. Actor, Interdependency and Frames and network management indicators have been implemented by actors, but institutional features and Interaction & Complexity: output has not been maximized by actors. In addition, the driving factor for the formation of network governance is the actor's own internal motivation to seek to increase the HDI of women. The advice given in this study is that actors can make regulations governing the sustainability of the network, network long-term planning, and the need for programs that are integrated in all dimensions of HDI.